2004
DOI: 10.1021/tx0340706
|View full text |Cite
|
Sign up to set email alerts
|

Detection of O6-Carboxymethyl-2‘-deoxyguanosine in DNA Following Reaction of Nitric Oxide with Glycine and in Human Blood DNA Using a Quantitative Immunoslot Blot Assay

Abstract: Previous research has shown that a range of nitrosated glycine derivatives react with DNA to form O6-carboxymethylguanine and O6-methylguanine DNA adducts [Harrison et al. (1999) Chem. Res. Toxicol. 12, 106-111). Nitrosated glycine derivatives may be formed in the gastrointestinal tract from the reaction of dietary glycine with nitrosating agents. The aim of this study was to further investigate the role of dietary glycine in the formation of O6-guanine adducts at physiologically relevant concentrations. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 18 publications
1
77
0
2
Order By: Relevance
“…The highest adduct levels were measured in the sigmoid colon and rectum. [11][12][13] Moreover, levels of O 6 -CMG from exfoliated colon cells have been shown to increase with increased meat consumption. 12-14 O 6 alkylguanine (O 6 -alkylG) adducts, especially O 6 -MeG, are primarily repaired by O 6 -methylguanine DNA methyltransferase (MGMT) via direct damage reversal.…”
mentioning
confidence: 99%
“…The highest adduct levels were measured in the sigmoid colon and rectum. [11][12][13] Moreover, levels of O 6 -CMG from exfoliated colon cells have been shown to increase with increased meat consumption. 12-14 O 6 alkylguanine (O 6 -alkylG) adducts, especially O 6 -MeG, are primarily repaired by O 6 -methylguanine DNA methyltransferase (MGMT) via direct damage reversal.…”
mentioning
confidence: 99%
“…The analysis of O 6 CMdG in blood was also investigated in volunteers that had consumed high levels of processed (nitrite-preserved red) meat compared to a vegetarian diet in a small scale pilot study. Previous research had identified the presence of the O 6 CMdG adduct in volunteers consuming a high red meat diet (20) and established that processed meat leads to higher levels of DNA damage than red meat (23). Thus, the present study sought to identify differences in O 6 CMdG adducts between a diet high in processed meat compared to a vegetarian diet.…”
Section: Introductionmentioning
confidence: 92%
“…The ISB has since been used to detect the M 1 dG adducts in mice livers (17) and human colorectal mucosa (18) and more recently we applied this methodology to the measurement of O 6 -carboxymethyl-deoxyguanosine adducts (O 6 CMdG, Fig. 1), using a polyclonal antibody (19), derived from nitrosated amines, for in vitro studies and in human blood samples of volunteers consuming a high red meat diet (20). The latter was confirmed by alternative qualitative methods of measuring O 6 CMdG (21).…”
Section: Introductionmentioning
confidence: 99%
“…Glycine ethyl ester.HCl (0.99 g, 7.09 mmol) was dissolved in water (1.8 cm 3 ) and dichloromethane (4 cm 3 ), stirred and cooled to -10° C. Aq. sodium nitrite (4.43 M, 1.8 cm 3 ) was added to the cooled solution, then 5% H 2 SO 4 (0.65 cm 3 ) was added dropwise and the solution stirred for 10 mins.…”
Section: Ethyl Diazoacetatementioning
confidence: 99%
“…One such adduct is O 6 -carboxymethyl-2'-deoxyguanosine (O 6 CMdG) that has been linked to nitrosated amines from red meat diets [2] . Previous research has examined this adduct using an immunoslot blot assay which is very sensitive but only a single adduct can be analysed at a time and difficulties can occur due to cross-reactivity of the antibodies [3,4] . A limited supply of a polyclonal antibody does exist for O 6 CMdG but attempts to produce a monoclonal antibody have been unsuccessful and a different technique will therefore be needed in the future.…”
mentioning
confidence: 99%